Crop rotations increased soil ecosystem multifunctionality by improving keystone taxa and soil properties in potatoes - Li, Qing-mei; Zhang, Dai; Zhang, Ji-zong; Zhou, Zhi-jun; Pan, Yang; Yang, Zhi-hui; Zhu, Jie-hua; Liu, Yu-hua; Zhang, Li-feng (Frontiers in Microbiology, 2023)
Continuous cropping of the same crop leads to soil degradation and a decline in crop production, and these impacts could be mitigated through rotation cropping. Although crop rotation enhances soil fertility, microbial community diversity, and potato yield, its effects on the soil ecosystem multifunctionality (EMF) remain unclear. In the present research, we comparatively examined the effects of potato continuous cropping (PP) and rotation cropping [potato–oat rotation (PO) and potato–forage maize rotation (PFM)] on the soil EMF as well as the roles of keystone taxa, microbes abundance, and chemical properties in EMF improvement. It was demonstrated that soil EMF is increased in rotation cropping (PO and PFM) than PP. Soil pH was higher in rotation cropping (PO and PFM) than in PP, while total phosphorus (TP) and available phosphorus (AP) were significantly decreased than that in PP. Rotation cropping (PO and PFM) markedly changed the bacterial and fungal community compositions, and improved the potential plant-beneficial fungi, e.g., Schizothecium and Chaetomium, while reducing the abundances of the potentially phytopathogenic fungi, e.g., Alternaria, Fusarium, Verticillium dahiae, Gibberella, Plectosphaerella, Colletotrichum, Phoma, and Lectera in comparison with PP. Also, co-occurrence patterns for bacteria and fungi were impacted by crop rotation, and keystone taxa, e.g., Nitrospira.1, Lysinibacillus, Microlunatus.1, Sphingomonas.3, Bryobacter.1, Micromonospora, and Schizothecium, were enriched in PO and PFM than PP. The structural equation model (SEM) further demonstrated that cropping systems increased soil ecosystem multifunctionality through regulating SOM and keystone taxa (Schizothecium1), and keystone taxa were mediated by soil pH. This study suggested that rotation cropping might contribute to the improvement of soil ecosystem multifunctionality as well as the development of disease-suppressive soils in comparison with potato continuous cropping.